Genetic Variation in Low-To-Medium-Affinity Fcγ Receptors: Functional Consequences, Disease Associations, and Opportunities for Personalized Medicine - Nagelkerke, Sietse Q.; Schmidt, David E.; de Haas, Masja; Kuijpers, Taco W. (Frontiers in Immunology, 2019)
Fc-gamma receptors (FcγR) are the cellular receptors for Immunoglobulin G (IgG). and Upon binding of complexed IgG, FcγRs can trigger various cellular immune effector functions, thereby linking the adaptive and innate immune systems. In humans, six classic FcγRs are known: one high-affinity receptor (FcγRI) and five low-to-medium-affinity FcγRs (FcγRIIA, -B and -C, FcγRIIIA and -B). In this review we describe the five genes encoding the low-to-medium -affinity FcγRs (FCGR2A, FCGR2B, FCGR2C, FCGR3A and FCGR3B), including functionally relevant single nucleotide polymorphisms (SNPs), haplotypes as well as copy number variants (CNVs), which occur in distinct copy number regions across the locus. Importantly, we recommend a consistent nomenclature of genetic variants in the FCGR2/3 locus. Next, we focus on the relevance of genetic variation in the FCGR2/3 locus in auto-immune and auto-inflammatory diseases, highlighting pathophysiological insights that are informed by genetic association studies. Finally, we illustrate how specific FcγR variants relate to variation in treatment responses and prognosis amongst autoimmune diseases, cancer and transplant immunology, suggesting novel opportunities for personalized medicine.